ANALISIS KAUSALITAS ANTARA PERTUMBUHAN EKONOMI, SEKTOR PARIWISATA, KETIMPANGAN DISTRIBUSI PENDAPATAN DAN KEMISKINAN DI KABUPATEN BADUNG - Wiradnyana, I Komang; Bendesa, I K.G. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.07.TAHUN.2021DO - 10.24843/EEB.2021.v10.i07.p06, 2021)
Economic growth, the tourism sector, inequality in income distribution and poverty are economic variables used to see the success of a region's development. The purpose of this study was to determine the relationship between the independent variables, namely economic growth, the tourism sector, inequality in income distribution, and the dependent variable on poverty in Badung Regency. This study uses secondary data with multiple linear regression analysis techniques, and previously conducted the Granger causality test to see the causal relationship between variables. The results showed that simultaneously economic growth, the tourism sector and inequality had a significant effect on poverty. Partially only the tourism sector that affects poverty. The results of the Granger causality analysis show that there is a one-way relationship between the tourism sector and poverty, there is no causality relationship between poverty and economic growth and there is no causality relationship between income inequality and poverty.